Addressing the challenges of implementing a Health Technology Assessment Policy Framework in South Africa. (13th August 2020) - Mueller, Debjani
Abstract : Objective: South Africa's commitment to progressively achieve universal health coverage can lead to the effective and appropriate use of Health Technology Assessment (HTA) to strengthen the healthcare system. The study aimed to analyze the challenges faced in the formal implementation and utilization of HTA in the public health sector. Methods: Review and analysis of health technology policies and legislation introduced in South Africa since 1965 serves as the backbone of this study. Walt and Gilson's health policy triangle framework and Kingdon's model were used for data analysis. In addition, a semi-structured survey was conducted among key stakeholders, including those attending HTA workshops that were held in 2016 and 2017. Results: The document review identified appropriate legislative and policy framework for informing healthcare decisions. Survey participants ( n = 55) reported limited political support, local capacity, and awareness of HTA as barriers to implementing HTA. They noted that adequate financial resources and availability and sharing of quality data are primary drivers for HTA development. Effective governance, collaboration, and cooperation between key stakeholders of the healthcare system were suggested as possible ways forward for the institutionalization of HTA. Conclusion: The South African government's goal to introduce the national health insurance program provides an excellent opportunity to formally introduce the use of HTA in decision making. Individual capacity development supported by institutional and organizational environments is urgently needed to achieve its full potential.